1992
DOI: 10.1128/jb.174.8.2560-2564.1992
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Pseudomonas fluorescens deficient in dissimilatory nitrite reduction are also altered in nitric oxide reduction

Abstract: Five Tn5 mutants of Pseudomonas fluorescens AK-15 deficient in dissimilatory reduction of nitrite were isolated and characterized. Two insertions occurred inside the nitrite reductase structural gene (nirS) and resulted in no detectable nitrite reductase protein on a Western immunoblot. One mutant had TnS inserted inside nirC, the third gene in the same operon, and produced a defective nitrite reductase protein. Two other mutants had insertions outside of this nir operon and also produced defective proteins. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…These results suggest that nitrite reduction is an obligatory requirement for nirK and nor operon expression. The coupling of nitrite reductase activity to the expression of nitrite and nitric oxide reductase has been observed in other denitrifiers (34,39).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that nitrite reduction is an obligatory requirement for nirK and nor operon expression. The coupling of nitrite reductase activity to the expression of nitrite and nitric oxide reductase has been observed in other denitrifiers (34,39).…”
Section: Discussionmentioning
confidence: 99%
“…First, nirS: :Tn5 mutants of Pseudomonas fluorescens not only lose their nitrite reductase activity but also have a decreased NO reductase activity. At the same time the H,"O exchange pattern of mutant cells reducing "NO is drastically changed versus the wild type with nitritereducing capability ( Ye et al, 1992). Second, a putative regulatory gene, nirQ, has been identified in l?…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity of the promoter in the presence of gaseous NO was about a third that of strain PAO1. It has been reported that the in vivo activities of NIR and NOR couple with each other (Ye et al, 1992;Zumft, 1993). Deficiency in NIR activity causes low activity of NOR, and vice versa.…”
Section: No-responding Induction Of the Nosr Promotermentioning
confidence: 99%